DIMENSIONS OF ASEAN COOPERATION IN HEALTH DEVELOPMENT OF SOUTHEAST ASIA - Anwar, Arman (Indonesian Journal of International Law, 2012)
With respect to the conditions of the health sector of Southeast Asian countries, according to the WHO, Southeast Asia was a region accounting for nearly a third of maternal and child mortality globally. This region was also an epidemic area of the HIV/AIDS. Dengue Fever (DF) was also of concern to ASEAN health officials because the number of cases remained high. Through the Yogyakarta Declaration, signed on April 2002, Health Ministers of ASEAN countries declared HEALTHY ASEAN 2020. With this vision, ASEAN was about to make the Southeast Asian region as a center for health development in 2020 and to entirely ensure the creation of a physically and mentally healthy ASEAN community, living in harmony in an environment of safe Southeast Asia region.Today, 9 years after declared, an even distribution of health development in ASEAN region showed limited progress; instead, disparity was created. On the one hand, there were countries with highly dynamic level of health development; but, on the other hand, there were countries that were sluggish. On scrutiny, the problems were not overly different, the patterns of disease were also almost the same; but, why one country could be better in the handling compared to other Southeast Asian countries. In an effort to cultural binding and with respect to the economic growth gap among ASEAN member countries, the ASEAN Charter could be maximized as a bridge and inspiration to improve solidity and commitment to assist one another and to work together, not to be individualistic, but to be more open and mutually respectful and feel as part of the real ASEAN community (awareness on ASEAN).